Improving outcomes for marginalised rural families through a care navigator program. (7th May 2020) - Kirby, Sue; Edwards, Karen; Yu, Serena; van Gool, Kees; Powell‐Davies, Gawaine; Harris‐Roxas, Ben; Gresham, Ellie; Harris, Mark; Hall, Jane
Abstract: Issues addressed: Health promotion programs are based on the premise that health and well‐being is impacted by a person's living circumstances, not just factors within the health arena. Chronic health issues require integrated services from health and social services. Navigator positions are effective in assisting chronic disease patients to access services. This family program in a small rural town in Western New South Wales targeted marginalised families with children under five years of age with a chronic health issue. The navigator developed a cross‐sectoral care plan to provide services to address family issues. The study aimed to identify navigator factors supporting improved family outcomes. Methods: Participants included parent/clients (n = 4) and the cross‐sectoral professional team (n = 9) involved in the program. During the interview, participants were asked about their perspective of the program. Interview transcripts were thematically analysed informed by the Chronic Care Model underpinned by Health Promotion Theory. Results: The program improved client family's lives in relation to children's health and other family health and social issues. Trust in the care navigator was the most important factor for parents to join and engage with the program. The care navigator role was essential to maintaining client engagement and supporting cooperation between services to support families. Conclusion: Essential care navigator skills were commitment, ability to persuade and empower parents and other professionals. So what?: This descriptive study demonstrated the positive influence of the care navigator and the program on high risk families in a small isolated community. It can be adopted by other communities to improve life for families at risk.